Pharmacogenetics and Precision Medicine Approaches for the Improvement of COVID-19 Therapies - Biswas, Mohitosh; Sawajan, Nares; Rungrotmongkol, Thanyada; Sanachai, Kamonpan; Ershadian, Maliheh; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2022)
Many drugs without establishing clinical effectiveness or tailoring safety are being administered to tackle coronavirus disease 2019 (COVID-19) pandemic situations. Repurposing strategy might be more effective and successful if pharmacogenetic interventions are being considered in future clinical studies/trials. Although it is very unlikely that there is almost no pharmacogenetic data for COVID-19 drugs, however, from inferring the pharmacokinetic (PK)/pharmacodynamic (PD) properties and some pharmacogenetic evidence in other diseases/clinical conditions, it is highly likelihood that pharmacogenetic associations are also feasible in at least some COVID-19 drugs.We strongly mandate to undertake pharmacogenetic assessment for at least these drug-gene pairs (atazanavir-UGT1A1, ABCB1, SLCO1B1, APOA5; efavirenz-CYP2B6; nevirapine-HLA, CYP2B6, ABCB1; lopinavir- SLCO1B3, ABCC2; ribavirin-SLC28A2; tocilizumab-FCGR3A; ivermectin-ABCB1; oseltamivir-CES1, ABCB1; clopidogrel-CYP2C19, ABCB1, warfarin-CYP2C9, VKORC1; non-steroidal anti-inflammatory drugs (NSAIDs)-CYP2C9) in COVID-19 patients for advancing precision medicine. Molecular docking and computational studies are promising to achieve new therapeutics against SARS-CoV-2 infection.. Current situation in the discovery of anti-SARS-CoV-2 agents at four important targets from in silico studies has described and summarized in this review. Although natural occurring compounds from different herbs against SARS-CoV-2 infection are favourable, however, accurate experimental investigation of these compounds are warranted to provide insightsful information. Moreover, clinical considerations of drug-drug interactions (DDIs) and drug-herb interactions (DHIs) of the existing repurposed drugs along with pharmacogenetics (e.g., efavirenz and CYP2B6) and herbogenetics (e.g., andrographolide and CYP2C9) interventions, collectively called multifactorial drug-gene interactions (DGIs) may further accelerate the development of precision COVID-19 therapies in the real-world clinical settings.